Analisis Hubungan Status Gizi dengan Kejadian ISPA Pada Bayi 3-6 Bulan di Kabupaten Konawe Selatan Tahun 2014 - Sorumba, Muhamad Agusman (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2014)
According to WHO (2008) infant mortality is caused by Acute Respiratory Infection (ARI) by 19%. Data at the Ranomeeto Health Center showed that there were 155 infants aged 3-6 months with upper respiratory tract infections in 2013. In 2014 (January-July) 50 babies were infected with ARI and 29 of them were undernourished This study aims to analyze the relationship between nutritional status and the incidence of acute respiratory infections (ARI) in infants aged 3-6 months. This research is a descriptive analytic study with a Cross Sectional Study approach. The population in the study were all infants 3-6 months suffering from upper respiratory tract infections as many as 50 people and a sample of 50 people who were taken by Total Sampling. Data were obtained using a questionnaire and tested using the Chi-Square test. The conclusion in this study is that there is a weak relationship between nutritional status and the incidence of acute respiratory infections (ARI) in infants aged 3-6 months in the working area of ​​the Ranomeeto Public Health Center, Konawe Selatan Regency with a value of X2 hit = 5.82 < X2 table = 3, 84 and P=0.016. Suggestions for mothers to give colostrum to their babies, for mothers of babies to maintain the nutritional status of their babies by providing proper nutrition. For Educational Institutions so that the results of this study can be a reference for further researchers. For this public health center, it is hoped that it can provide information to the government and related agencies in determining policies and planning programs for overcoming upper respiratory tract infections